RELEVANCE OF RENÉ GIRARD’S THEORY IN FRIEDRICH DÜRRENMATT’S DRAMA “THE VISIT” - Choudhary, Dev Kumar; Guite, Chiinngaihkim (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human desire is essentially imitative, or mimetic, according to René Girard’s mimetic theory, rather than emerging naturally from inside. The scapegoat mechanism, according to Girard, is frequently used to manage rivalry and possible conflict that arises when people want what others want. Girard’s theory has ramifications for comprehending social dynamics, aggression, religious rituals, and other facets of human conduct. According to Girard, people do not choose what they want on their own. Rather, their "models" mimic the aspirations of others. A scapegoat mechanism may appear when rivalry and conflict over scarce resources or prestige result from mimetic desire. Like in the drama “The Visit” by Friedrich Dürrenmatt the protagonist Ill represented as scapegoat. Al the citizens unite against Ill and kill him for the prosperity of the society. His theory applied in number of fields like literature, religion and anthropology.